Crayfish shell biochar for the mitigation of Pb contaminated water and soil: Characteristics, mechanisms, and applications. (15th February 2021) - Sun, Tao; Xu, Yingming; Sun, Yuebing; Wang, Lin; Liang, Xuefeng; Jia, Hongtao
Abstract: Biochar has been widely used in the mitigation of soil potentially toxic metals due to its high efficiency and low cost. Crayfish shell biochar (CSBC) was prepared at 300, 500, and 700 °C (referred to as CS300, CS500, and CS700, respectively) and the performance and mechanism of CSBC for mitigating Pb polluted water and soil was investigated. The results indicated that CSBC prepared at higher temperatures possessed higher pH value and ash content, more abundant pore structure, and higher stability. Pb 2+ adsorption onto CSBC fitted well with the pseudo second order and intraparticle diffusion models. The maximum adsorption capacity of Pb 2+ increased with the pyrolysis temperature, being 599.70, 1114.53, and 1166.44 mg·g −1 for CS300, CS500 and CS700, respectively. Compared with the control soil samples, the content of available Pb after applying 0.05%–5% CSBC was reduced by 1.87%–16.48% in acidic soils and 1.00%–11.09% in alkaline soils. Moreover, the fractionation of exchangeable Pb was converted to stable organic matter bound, Fe-Mn oxide bound, and residue fractions. XRD, SEM-EDS, and FTIR analysis showed that ion exchange, complexation, precipitation, and C−π interaction are the dominant interaction mechanisms. Therefore, CSBC can employ as an effective immobilizing agent for the mitigation of Pb contaminated water and soil. Graphical abstract: Image 1 Highlights: Pyrolysis temperature affected the characteristics of crayfish shell biochar. Crayfish shell biochar showed high Pb 2+ sorption capacity (599.70–1166.44 mg·g −1 ). Main interaction mechanisms: precipitation, ion exchange, complexation, C–π interaction. Crayfish shell biochar could decrease Pb availability in acid and alkaline soil.